Influence of post-annealing treatment on the morphology of Au films deposited on liquid surfaces. (10th September 2019) - Ye, Ziran; Xu, Fengyun; Sun, Guofang; Yan, Bo; Gao, Fan; Cai, Pinggen; Lv, Bin; Li, Yun; Chen, Naibo; Wang, Ke; Ye, Gaoxiang
Abstract: We report the annealing effects on the morphology of metallic films deposited on liquid surfaces, which was enabled by depositing Au atoms to a silicone oil surface by thermal evaporation at room temperature. Due to the isotropic characteristics of the liquid surface, the growth of Au films on silicone oil surfaces follows the two-stage growth model. Ramified aggregates consist of substantial nanoparticles exist in the Au film, which is different from films fabricated on solid substrates. After annealing at different temperatures, small nanoparticles started to melt first, and formed liquid layers covered on adjacent large nanoparticles. As the annealing temperature increased, more nanoparticles melt and the liquid layer became thicker, resulting in the increase of mean diameter of Au nanoparticles and film coverage. The dependence between film morphology and annealing temperature was investigated. This work provides a potential mechanism of annealing effect on the morphology of metallic films deposited on free-sustained substrates.